2019
DOI: 10.1002/ente.201900037
|View full text |Cite
|
Sign up to set email alerts
|

Kilogram‐Scale Fabrication of Si/C Bean‐Structured Materials as Stable Anodes for Li‐Ion Storage

Abstract: The practical application of Si‐based materials is widely impeded by poor electrochemical cycling stability. Here, inspired by the compact cladding and close connection structure of beans, an efficient buffering bean‐structured material of Si/C framework as a stable anode for Li‐ion storage is designed. By a simple ball‐milling process, the kilogram‐scale production of the Si/C can be realized. The Si/C composites exhibit excellent enhancement of electrochemical performance with a large storage capacity (1162.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Alternative methodologies have been developed to address the limitations of simple physical mixing. Yang et al [22] have found that a composite of silicon and graphite synthesized through thermal pyrolysis of polyvinyl chloride dispersed with nanosized silicon and fine graphite particles displays a reversible capacity of approximately 700 mAh g −1 with improved cyclability compared to raw nanocrystalline Si. Additionally, ultrasonication combined with thermal treatment in a reducing atmosphere is another approach that has been explored for synthesizing silicon nanoparticles/graphene composites.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methodologies have been developed to address the limitations of simple physical mixing. Yang et al [22] have found that a composite of silicon and graphite synthesized through thermal pyrolysis of polyvinyl chloride dispersed with nanosized silicon and fine graphite particles displays a reversible capacity of approximately 700 mAh g −1 with improved cyclability compared to raw nanocrystalline Si. Additionally, ultrasonication combined with thermal treatment in a reducing atmosphere is another approach that has been explored for synthesizing silicon nanoparticles/graphene composites.…”
Section: Introductionmentioning
confidence: 99%